PESANTREN SEBAGAI MOTOR PENGGERAK PEMBERDAYAAN EKONOMI UMAT: EVALUASI MODEL PENDIDIKAN VOKASIONAL BERBASIS PESANTREN - Hoerul Umam; Aziz Mujadilah; Indra Kurnia (STKIP Subang, 2026)
This study aims to analyze the role of Islamic boarding schools (pesantren) as a driving force for community economic empowerment through an evaluation of a pesantren-based vocational education model. This study employed a qualitative approach with library research, using books, scientific journals, and relevant research findings as data sources, analyzed using content analysis techniques. The results indicate that Islamic boarding schools (pesantren) play a strategic role in economic empowerment through the development of productive business units, entrepreneurship education, and Sharia-based economic institutions. The pesantren-based vocational education model has proven effective in integrating practical skills with Islamic values, resulting in economically independent and character-based human resources. However, the model's effectiveness still faces challenges in managerial aspects, curriculum, and access to capital, resulting in suboptimal empowerment outcomes. Evaluatively, this study found that the success of Islamic boarding school economic empowerment is largely determined by the systematic integration of the vocational curriculum, professional business management, and the support of institutional networks. Therefore, this study's contribution lies in strengthening the pesantren-based vocational education model as a strategy for sustainable community economic empowerment.